Familial adult myoclonus epilepsy : a clinical, neurophysiological and genetic study of a familial form of myoclonic epilepsy - Carr, Jonathan (Stellenbosch : University of Stellenbosch, 2009)
Thesis (DMed (Medicine. Internal Medicine))--University of Stellenbosch, 2009.